13The Effectiveness of Inquiry-Based Learning in Fostering Students’ Problem-Solving Competence: Evidence from Secondary Education - Faizatul Qudriyah; Umar Manshur (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students’ character and higher-order thinking skills; however, learning practices at the junior high school level remain predominantly conventional and teacher-centered, resulting in limited stimulation of students’ problem-solving abilities. This study aims to (1) examine the implementation of the Inquiry-Based Learning (IBL) approach, (2) identify the challenges encountered by teachers, and (3) analyze its impact on students’ problem-solving skills in PAI learning. The research was conducted at Muhammad Shodiq Maron Middle School and Sunan Bonang Maron Middle School, located in Probolinggo, East Java, Indonesia. This study employed a qualitative method with a case study approach, utilizing data collection techniques such as observation, in-depth interviews, and documentation. Data validity was ensured through triangulation and member checking. The findings reveal that IBL is systematically implemented through several stages, including orientation, problem formulation, investigation, data analysis, and reflection. In this process, teachers function as facilitators who guide students in constructing knowledge, while students actively engage in critical inquiry, collaborative discussion, and problem-solving activities. Although several challenges were identified, particularly related to limited instructional time and varying levels of teacher readiness in designing inquiry-based activities, the implementation of IBL demonstrated significant positive outcomes. It enhanced students’ active participation, confidence in expressing ideas, critical thinking capacity, and ability to relate learning materials to real-life contexts. In conclusion, the IBL approach is effective in improving students’ problem-solving skills in PAI learning and fostering critical, reflective, and solution-oriented learners, making it highly relevant for 21st-century contextual education.